SMU and Synagie Partner to Upskill and Plug Skill Gaps In Southeast Asia's Ecommerce and Tech Workforce - Singapore Management University (Institutional Knowledge at Singapore Management University, 2022)
Leading digital commerce enabler in Southeast Asia, Synagie, and Singapore Management University (SMU) signed a Memorandum of Understanding (MoU) today to co-develop continuing education and training programmes. The programmes are specially designed to address the specific talent and skills shortages faced by the technology and eCommerce sector in Singapore and Southeast Asia, with the aim of upskilling over 3,000 sector professionals by 2025.